Evaluation of hydropower projects in Balkan Rivers based on direct sediment transport measurements; challenges, limits and possible data interpretation – Case study Vjosa River/Albania. (1st May 2022) - Pessenlehner, Sebastian; Liedermann, Marcel; Holzapfel, Patrick; Skrame, Klodian; Habersack, Helmut; Hauer, Christoph
Abstract: The Vjosa River in Albania represents one of Europe's last free‐flowing wild rivers, comprising a mosaic of various habitats and forming a highly dynamic natural ecosystem for flora and fauna, that has largely disappeared from other European rivers outside of Russia. However, due to economic interests, this sensitive and heterogeneous river system is under pressure from potential future use in hydropower, threatening the good hydromorphological and ecological status of the river with reservoir flushing, hydropeaking, colmation, loss of habitats and loss of connectivity. Beside the ecological impacts, this study aims to point out the boundaries for technical and economic issues related to hydropower. Hence, for the first time, sediment transport in the Vjosa River was measured. The results indicate possible consequences of a disturbed sediment regime and loss of capacity caused by the sedimentation of reservoirs. Moreover, subsequent consequences, such as river bed incision downstream of dams as well as progressive coastal erosion, are discussed. By combining data from direct bedload and suspended sediment measurements with long‐term hydrological data, an attempt is made to describe the sediment characteristics of the Vjosa catchment and evaluate potential hydropower plants and resulting reservoir sedimentation using limited data. Based on the presented study, it is aimed to define sediment monitoring standards for requested environmental impact assessments and to highlight possible negative impacts of hydropower projects across the entire Balkan region.